Evaluation of Salivary Secretory Immunoglobulin A Levels in Diabetic Patients and Association with Oral and Dental Manifestations - Shahla Kakoei; Bahareh Hosseini; Ali-Akbar Haghdoost; Mojgan Sanjari; Ahmad Gholamhosseinian; Vahid F. N. Afshar (Sultan Qaboos University Medical Journal, 2015)
Objectives: Oral and dental manifestations in diabetic patients can arise due to numerous factors, including elevated salivary secretory immunoglobulin A (s-IgA) levels. This study aimed to evaluate s-IgA concentrations in patients with type 2 diabetes mellitus (T2DM) and to investigate the association between s-IgA levels and oral and dental manifestations of T2DM. Methods: This cross-sectional descriptive study was carried out between October 2011 and September 2012 in Kerman, Iran, and included 260 subjects (128 patients with T2DM and 132 healthy controls). Unstimulated salivary samples were collected from all subjects and s-IgA levels were determined using the immunoturbidimetric method. The oral cavities and teeth of T2DM patients were evaluated for oral and dental manifestations. Results: Both diabetic and control subjects with higher concentrations of s-IgA had significantly higher numbers of decayed, missing or filled teeth (DMFT) and periodontal index (PDI) scores (P <0.050). s-IgA levels were significantly higher in subjects with oral candidiasis (P <0.050). Among diabetic patients, significantly higher s-IgA levels were concomitant with xerostomia and denture stomatitis (P ≤0.050). There were no significant differences between s-IgA concentrations and other oral or dental manifestations in either group. Conclusion: Individuals with a greater number of DMFT, a higher PDI score and oral candidiasis had significantly higher s-IgA levels. s-IgA levels were not significantly higher among diabetic patients in comparison to the control group. However, significantly higher s-IgA levels occurred with xerostomia and denture stomatitis in diabetic patients. In addition, s-IgA was significantly higher in patients with uncontrolled diabetes compared to those with controlled diabetes.